Child-friendly school-based learning management model for health and physical education - Sunardianta, Raden; Diat Prasojo, Lantip; Yuliarto, Hari; Firmansyah, Firmansyah (LPMPP Universitas Negeri Yogyakarta, 2024)
Developing learning management models is crucial to address the diverse needs of effective learning while promoting active participation, preventing discrimination, and safeguarding students' rights and responsibilities in line with their growth. This article aims to create a child-friendly school-based learning model for health and physical education in elementary schools and validate it through expert assessments. Following Brog and Gall's model development approach, data collection involved assessment questionnaires administered to various stakeholders, including school supervisors, principals, teachers, students, and committees. The findings underscore the importance of incorporating diverse learning methods, adequate infrastructure, gender sensitivity, and meaningful learning experiences into the model. The three sequential stages' assessment results demonstrate the proposed model's high feasibility, scoring consistently high across stages. Referred to as a model, this innovative model showcases significant promise, suggesting further refinement to ensure its efficacy in addressing multifaceted learning requirements, fostering inclusive participation, and upholding students' rights and obligations per their developmental stage. This study highlights the need for evolving learning management models to cater to diverse educational needs effectively.